2003
DOI: 10.1073/pnas.0536856100
|View full text |Cite
|
Sign up to set email alerts
|

Dietary restriction normalizes glucose metabolism and BDNF levels, slows disease progression, and increases survival in huntingtin mutant mice

Abstract: In addition to neurological deficits, Huntington's disease (HD) patients and transgenic mice expressing mutant human huntingtin exhibit reduced levels of brain-derived neurotrophic factor, hyperglycemia, and tissue wasting. We show that the progression of neuropathological (formation of huntingtin inclusions and apoptotic protease activation), behavioral (motor dysfunction), and metabolic (glucose intolerance and tissue wasting) abnormalities in huntingtin mutant mice, an animal model of HD, are retarded when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
289
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 388 publications
(304 citation statements)
references
References 62 publications
(60 reference statements)
14
289
0
1
Order By: Relevance
“…Nevertheless, the PMRS was capable of responding to an environmental condition (CR) that preserves brain function during aging. Previous studies have shown that neurons in the brains of rats and mice maintained on CR regimens are relatively resistant to oxidative and metabolic stress compared with control animals fed AL in models of Alzheimer's disease, Parkinson's disease, Huntington's disease, and stroke (18,19,22,53). The mechanism by which CR protects neurons against oxidative injury is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the PMRS was capable of responding to an environmental condition (CR) that preserves brain function during aging. Previous studies have shown that neurons in the brains of rats and mice maintained on CR regimens are relatively resistant to oxidative and metabolic stress compared with control animals fed AL in models of Alzheimer's disease, Parkinson's disease, Huntington's disease, and stroke (18,19,22,53). The mechanism by which CR protects neurons against oxidative injury is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…CR has been shown to lower the rate of production of free radicals by mitochondria and to protect cells against oxidative stress (12)(13)(14)(15)(16)(17), a mechanism consistent with the free radical theory of aging. CR can attenuate age-related deficits in brain function and can protect neurons against dysfunction and death in animal models of Alzheimer's disease, Parkinson's disease, Huntington's disease, and stroke (11,(18)(19)(20)(21)(22). The mechanisms by which CR protects brain cells during aging are unknown but may involve induction of the expression of neurotrophic factors (20,23), protein chaperones (22), and mitochondrial uncoupling proteins (24).…”
mentioning
confidence: 99%
“…All mice were housed under standard conditions with free access to food and water for 24 h, and 12-h light/dark cycle. We used male N171-82Q HD mice for all our studies since we found that there is significant variability in all phenotypes between male and female N171-82Q mice (Duan et al 2003). N171-82Q male mice usually develop motor performance deficit after 19 weeks of age; the average life-span in these mice is about 22 weeks.…”
Section: Mice and Drug Administrationmentioning
confidence: 99%
“…Activation of adaptive stress responses in animal models of neurodegenerative diseases have been able to provide benefits in cognition and motor function, and suggest that these molecular pathways maybe able to be activated through cognitive stimulation, exercise, and CR (41,42,67,76,108,125). One of the key factors that may help protect against the decline of cognitive function in aging and disease is BDNF.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%